Compliant Titin Isoform Content Is Reduced in Left Ventricles of Sedentary Versus Active Rats - Chung, Charles S.; Hiske, Mark A.; Chadha, Arjun; Mueller, Patrick J. (Frontiers in Physiology, 2020)
A sedentary lifestyle is associated with increased cardiovascular risk factors and reduced cardiac compliance when compared to a lifestyle that includes exercise training. Exercise training increases cardiac compliance in humans, but the mechanisms underlying this improvement are unknown. A major determinant of cardiac compliance is the compliance of the giant elastic protein Titin. Experimentally reducing Titin compliance in animal models reduces exercise tolerance, but it is not known whether sedentary versus chronic exercise conditions cause differences in Titin isoform content. We hypothesized that sedentary conditions would be associated with a reduction in the content of the longer, more compliant N2BA isoform relative to the stiffer N2B isoform (yielding a reduced N2BA:N2B ratio) compared to age-matched exercising controls. We obtained left ventricles from 16-week old rats housed for 12 weeks in standard (sedentary) or voluntary running wheel (exercised) housing. The N2BA:N2B ratio was decreased in the hearts of sedentary versus active rats (p=0.041). Gene expression of a titin mRNA splicing factor, RNA Binding Motif 20 protein (RBM20), correlated negatively with N2BA:N2B ratios (p=0.006, r=-0.449), but was not different between groups, suggesting that RBM20 may be regulated post-transcriptionally. Total phosphorylation of cardiac Titin was not different between the active and sedentary groups. This study is the first to demonstrate that sedentary rats exhibit reduced cardiac Titin N2BA:N2B isoform ratios, which implies reduced cardiac compliance. These data suggest that a lack of exercise (running wheel) reduces cardiac compliance and that exercise itself increases cardiac compliance.